In vivo encystation of Blastocystis hominis - Suresh, K.; Venilla, G.D.; Tan, T.C.; Rohela, M. (2009)
Blastocystis from infected stools of a person who showed chronic symptoms of abdominal discomfort and diarrhea were examined over a 6-month period, using transmission electron microscopy, for the ultrastructural changes from vacuolar to cystic stage. The study confirms the irregular shedding phenomenon of the organism previously reported, and for the first time, records sequential changes in encystation in stools collected over a time period. The study also confirms the existence of a precystic stage which has an immature cell wall consisting of a layer of a homogenous electron-dense mass surrounding the cell which acts as a intermediatory stage between the vacuolar and cystic stage.